Clinical value of human papillomavirus E6/E7 mRNA testing in patients with atypical squamous cells of undetermined significance and low-grade squamous intraepithelial lesion - Qing Wang; Cai-Ying Zhu; Li-Mei Chen; Shu-Jun Gao; Ming Du; Hong-Wei Zhang; Hua Feng; Yu Song; Wen-Jing Diao; Yan-Yun Li; Long Sui (Reproductive and Developmental Medicine, 2018)
Objective: To explore the clinical significance of the quantitative detection of human papillomavirus (HPV) E6/E7mRNA in triage of patients with atypical squamous cells of undetermined significance (ASC-US) and low-grade squamous intraepithelial lesion (LSIL). Methods: A cross-sectional screening study was conducted among women who underwent outpatient gynecological screening at the Obstetrics and Gynecology Hospital of Fudan University from September 2015 to July 2016. A total of 500 patients from our hospital with ASC-US or LSIL based on cytology testing were subjected to HPV DNA and HPV E6/E7 mRNA quantitative analysis. Results: The specificity of the HPV E6/E7 mRNA test for detecting ≥ high-grade squamous intraepithelial lesion (HSIL+) was statistically higher than that of the HPV DNA test (61.3% vs. 40.0%, P < 0.05), whereas there was no significant difference in the sensitivity of HPV E6/E7 mRNA test and HPV DNA test (90.0% vs. 95.0%, P > 0.05). The positive rates of HPV in the participants tested by HPV E6/E7 mRNA and HPV DNA were, respectively, 42.8% (214/500) and 62.8% (314/500), with statistical significance (P < 0.05). Conclusions: The HPV E6/E7 mRNA test was slightly less sensitivity than that of the HPV DNA test for diagnosing HSIL+ in patients with ASC-US and LSIL, but the difference was not significant, although the specificity of the former was significantly higher. HPV E6/E7 mRNA detection can effectively reduce overdiagnosis and overtreatment of patients with ASC-US and LSIL and has important clinical value in triage of patients with ASC-US and LSIL.